G1 Resource profiles, extrapolation domains, and land-use patterns - Nelson, Andrew (2011)
The Ganges Basin Development Challenge (BDC) research program will focus on brackish-water coastal zones in the Ganges Basin, where agricultural lands have a maximum salinity greater than 5 ppt (parts per thousand) in the dry season (salinity is lower in the wet season). The BDC vision of success requires innovations in water governance, improved availability of dry-season water, improved practices for managing salt-affected lands, and intensification and diversification of farm systems. In short, the program requires technological innovation and effective dissemination of those technologies. Before a technology can be disseminated beyond the study site where it is developed, it is important to identify its “extrapolation domain.” This requires matching the resource profile of an area with the resource requirements of a technology. The goals of these technologies—increased resilience, improved livelihoods, increased production—also require an understanding of how can the land in the coastal zones best be zoned and used to meet different goals and objectives? And, how should land use change for anticipated hydrological change scenarios? This project aims to answer the question of “what works where” now and under climate change scenarios.